Abortion Reviewed From Islamic Law and Positive Law in Indonesia: Government Regulation No. 61 of 2014 about Reproductive Health - Mulkan Nasution; Pagar Pagar; Ansari Yamamah (AT-TAFAHUM: Journal of Law, 2017)
In mid-2014, the Indonesian government, through the Ministry of Health of the Republic of Indonesia, issued Government Regulation No. 61 of 2014 concerning Reproductive Health as a derivative regulation/mandate of Law No. 36 of 2009 concerning Health. This regulation contains nine articles governing abortion, which was previously a criminal offense regulated in the Criminal Code with a maximum penalty of fifteen years. In this regulation, the government provides exceptions for abortion based on two reasons: 1). Due to indications of medical emergency, and 2). Due to pregnancy resulting from rape, and can be performed if the gestational age is no more than forty days calculated from the first day of the last menstrual period. In Islamic law, abortion without old ageis a prohibited act. Scholars have agreed that abortion is prohibited if the fetus is one hundred and twenty days old and the soul has been breathed into it. This is based on a hadith narrated by Bukhari and Muslim which states that after the fertilization phase, mugah(120 days), an angel was sent to her and the soul was breathed into her. Regarding the permissibility of abortion before the gestational age of one hundred and twenty days, scholars have different opinions, Imam al-Ghazali and Imam al-Dusuqi prohibit abortion when the male sperm and the female ovum have mixed in the uterus, while Ibn 'Abidin permits abortion until the fetus is one hundred and twenty days old and the soul has been breathed into it. The middle opinion between the two groups is Ibn Rajab who permits abortion with a time limit of up to forty days of fetal age. This research is a descriptive normative juridical research with a comparative legal research approach that uses qualitative research methods. The tools and techniques for data collection are carried out by tracing laws and other legal sources from the legal system that are considered relevant to the main issue at hand